2019
DOI: 10.1111/imcb.12241
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–macrophage cooperation and its impact on tissue repair

Abstract: Immune cells are rapidly recruited to a site of injury or infection. Although the importance of phagocytic immune cells in clearing bacteria has long been appreciated, the advent of technologies allowing more in‐depth analysis of cellular function, such as intravital microscopy and the use of genetically modified animal models, has allowed much deeper insight into the complex roles of these cells play during tissue repair. Many immune cells contribute to the repair process; however, this review will concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 70 publications
(140 reference statements)
1
50
0
1
Order By: Relevance
“…Wound healing is a complex process that involves extracellular matrix components, fibroblasts and immune cells such as neutrophils and macrophages (Yoon et al, 2018;Bouchery and Harris, 2019;Kreimendahl et al, 2019;Paganelli et al, 2020). The first set of our studies focused on establishing the wound healing effects of FB (lipids + proteins), in vivo, using an experimental rat model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wound healing is a complex process that involves extracellular matrix components, fibroblasts and immune cells such as neutrophils and macrophages (Yoon et al, 2018;Bouchery and Harris, 2019;Kreimendahl et al, 2019;Paganelli et al, 2020). The first set of our studies focused on establishing the wound healing effects of FB (lipids + proteins), in vivo, using an experimental rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies showed that F6 promotes the death of cancer cells by regulating cellular signalling and inducing apoptosis (Al-Hassan et al, 2019). Since F6 promotes fibroblast migration and death in cancer cells, this lipid species carries cell-specific activities in different types of cells immune cells such as neutrophils are essential for recognizing injured cells while macrophages are essential for removing dead cells from the wounds (Yoon et al, 2018;Bouchery and Harris, 2019;Opneja et al, 2019). FB treatment promoted macrophage recruitment to the rat dermal wound sites, in vivo (wound resolving late stages; Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 ). It activates the synthesis of lipoxins, DHA products, and E series resolvins and decreases their production of classical eicosanoids 39,40 . These pro-resolving lipid mediators collectively reduce vascular permeability, inhibit further neutrophil transmigration, promote recruitment of nonphlogistic monocytes, induce neutrophil apoptosis and promote their efferocytosis, creating a positive feedback in favor of resolution.…”
Section: Clearance Of Apoptotic Neutrophilsmentioning
confidence: 99%
“…derivatives from arachidonic acid—that participate in creating an environment critical for tissue repair. Finally, in our own contribution to the Special Feature, we tackle the important concept of neutrophil–macrophage cooperation in wound healing, suggesting that targeting their intercellular crosstalk could offer new opportunities for the therapeutic treatment of tissue injuries.…”
mentioning
confidence: 99%